Analysis of Current Ratio, Debt Ratio, Net Profit Margin, and Total Asset Turnover Change in Income (Study of Multinational Companies Listed on the IDX for the 2020-2022 Period) - Handayani, Sutri; Suhardjanto, Djoko; Muhtar, E; Honggowati, Setianingtyas (Ilomata International Journal of Tax and Accounting, 2023)
A change in profit is a condition in which a company over a period of time has an increase or decrease in profits compared to the previous period. Failure to make a profit will seriously affect business operations. In the short term, losses may not matter unless the business suffers a substantial loss. The purpose of this research is to empirically examine if the ratios of current, debt, net profit margin, and total asset turnover have a significant impact on the growth of income for MNCs included in the IDX index between the years 2020 and 2022. This kind of study is quantitative and makes use of already collected data. For the years 2020-2022, this research focuses on American MNCs trading on the Indonesia Stock Exchange (IDX). A total of 68 samples were collected for this investigation through a purposive sampling strategy. Several different types of statistical tests (descriptive, multiple regression, traditional, and hypothesis) were utilized to analyze the data for this study. This research found that although changes in the Debt Ratio, Net Profit Ratio, and Total Asset Turnover did impact profits, Current Ratio no effect on profits. financial development. In addition, the findings demonstrate that the ratios of current, debt, net profit margin, and total asset turnover all have a synergistic impact on the rate at which income fluctuates.